Associação entre consumo de alimentos ultraprocessados e marcadores inflamatórios em adolescentes de escolas públicas em São Luís-Ma - MARTINS, Glauciane Márcia dos Santos (2018)
INTRODUCTION: Excessive consumption of ultraprocessed foods has been reported as one of the main causes of Chronic Noncommunicable Diseases (NCD), which are related to chronic low-level inflammatory processes. OBJECTIVE: To evaluate the consumption of ultraprocessed foods and its relation with inflammatory markers. METHODS: A crosssectional study was performed with 391 adolescents from public schools, both sexes, between 17 and 18 years old in São Luís-MA, a capital of northeastern Brazil. Food consumption was evaluated by means of two 24-hour reminders and categorized into three groups: in natura or minimally processed, including ingredients and culinary preparations; processed; and ultraprocessed, according to the NEW classification. The inflammatory markers evaluated were adiponectin, interleukin-6 (IL-6), interleukin-8 (IL-8), C-reactive protein (CRP) and tumor necrosis factor (TNF-α). The hierarchical linear regression was used to verify the association between inflammatory markers and the percentage of ultraprocessed caloric contribution. RESULTS: The mean age of adolescents was 17.3 years (± 0.49DP), of which 57.0% were female. The average daily energy consumed was of 1991.0 kcal/day, with 26.1% of the calories coming from ultraprocessed foods, with emphasis on the consumption of cakes, pies and sweet biscuits (5.7%), salty crackers and chips chips (4.4%) and fast food snacks (4.1%). It was observed that in the upper tertile of ultraprocessed consumption there was higher intake of carbohydrate, lipids, saturated fat and sodium intake while there was less intake of protein, fiber, vitamin D and B6 intake. The median (p25-p75) of the inflammatory markers were: adiponectin - 0.04 mg/l (0.03 - 0.06); IL-6 - 1.2 mg/l (0.7-2.0); TNF-α, 2.8 mg/l (1.7-4.1); IL-8, 27.1 mg/l (10.7-60.7) and PCR, 0.1 mg/l (0.0-0.3). After adjusted analysis, there was a direct association between IL-8 and the percentage of ultraprocessed caloric contribution. CONCLUSIONS: The higher consumption of ultraprocessed foods was related to poorer diet quality and higher levels of IL-8.